Prevalence, awareness, treatment and control of diabetes and impaired fasting glucose in the Southern Cone of Latin America. - Vilma Irazola; Adolfo Rubinstein; Lydia Bazzano; Matias Calandrelli; Chen Chung-Shiuan; Natalia Elorriaga; Laura Gutierrez; Fernando Lanas; Jose A Manfredi; Nora Mores; Hector Olivera; Rosana Poggio; et al. (PLoS ONE)
Aims To determine the prevalence, treatment and control of diabetes mellitus (DM) and impaired fasting glucose (IFG) as well as associated factors in the adult population of four cities of the Southern Cone of Latin America (SCLA). Methods This is a cross-sectional population-based study that included 7407 adults between 35 and 74 years old in four cities of the SCLA: Temuco (Chile), Marcos Paz and Bariloche (Argentina), and Pando-Barros Blancos (Uruguay). DM was defined as fasting plasma glucose ≥126 mg/dL or self-reported history of diabetes. Awareness, treatment, and control of DM were defined as subjects self-reporting a DM previous diagnosis, the use of a prescription medication or nonpharmacological intervention for DM, and fasting plasma glucose <126 mg/dl, respectively. Results Prevalence of DM varied among cities, between 8.4% in Bariloche and 14.3% in Temuco. Prevalence of IFG varied at different sites, from 3.5% in Barros Blancos to 6.8% in Marcos Paz. Of the total number of people with diabetes, 20% were newly diagnosed at the time of the study. Overall, 79.8% of patients with diabetes were aware of their condition. The treatment and control rate were 58.8% and 46.2%, respectively. Older age, family history of diabetes, lower educational attainment, overweight, obesity, central obesity, low physical activity, hypertension, hypercholesterolemia and hypertriglyceridemia were all significantly associated with an increased risk of diabetes. Conclusions The prevalence of DM and IFG in the adult population of the SCLA is high and varies among cities. These conditions represent a public health challenge since the rates of awareness, treatment, and control are still low.